Rare‐Earth Doping Transitional Metal Phosphide for Efficient Hydrogen Evolution in Natural Seawater. Issue 3 (8th December 2022) - Wu, Xianhong; Qiu, Jieshan; Wang, Zhiyu
Abstract : Electrolysis of inexhaustible seawater offers a promising way for harvesting practically infinite hydrogen energy without worsening freshwater shortage. Complicated ionic environment of saline seawater, however, places a great burden on catalyst performance for hydrogen evolution. Herein, tailoring the electronic structure of transitional metal phosphide by rare‐earth doping for effectively propelling hydrogen evolution in a wide pH range and natural seawater is reported. The rare‐earth doping leads to not only a nearly zero Gibbs free energy of H* adsorption and lower work function but also faster OH* desorption for rapid release of the active sites, thereby accelerating the hydrogen evolution reaction (HER) kinetics under nonacidic conditions. On this basis, highly conductive and hydrophilic MXene is introduced to further boost the adsorption of hydrogen carriers and charge transfer across the catalyst. Together, they allow the activity, kinetics, and durability of the electrocatalyst for HER to be improved overall. The obtained electrocatalyst shows superior activity to commercial Pt/C in terms of specific surface area and active mass and turnover frequency, as well as 400 times longer lifetime than Pt/C with high Faradaic efficiency in natural seawater. This study presents new insight into the development of viable electrocatalysts for harvesting hydrogen energy from abundant‐reserve seawater. Abstract : A rare‐earth doping strategy is developed to weaken the adsorption of both H and OH intermediates on transitional metal phosphide for boosting hydrogen evolution reaction. It enables highly active and stable electrocatalysts for hydrogen production in a wide pH range and complex ionic environment of natural seawater.